Dentoskeletal effects of miniscrew-anchored maxillary protraction: Evaluating the role of mandibular anchorage bar and night facemask - Manhães, Fernando Rayes; Pereira da Silva, Tafnes; André, Cristiane Barros; Valdrighi, Heloísa Cristina; Carmo de Menezes, Carolina [UNESP]; Vedovello, Silvia A.S. (Elsevier, 2025)
Introduction: This study evaluated the dentoskeletal effects of miniscrew-anchored maxillary protraction, which included a mandibular anchorage bar and a night facemask in adolescents. Methods: A total of 20 growing patients with Class III malocclusion and maxillary deficiency were treated with a hybrid hyrax expander with 2 miniscrews in the maxilla and a mandibular anchor bar supported in 2 miniscrews in the anterior region of the mandible. Class III elastics were used from the maxillary first molars to the mandibular anchorage bar, joining the mandibular miniscrews installed between permanent incisors and canines. The variables that met the presuppositions of a parametric analysis were analyzed using the paired t test, and the remaining variables were analyzed using the nonparametric Wilcoxon paired test. Results: The final sample included 17 subjects (4 females and 13 males; initial age, 12.3 ± 1.2 years). The results demonstrated a significant increase in Wits appraisal (mm), ANB (°), SNA (°), N perp-A (mm), Co-A (mm), Co-Gn (mm), AFAI (mm), molar relationship (mm), overjet (mm), U6-vertical Pt (mm), L1-NB (mm) and U1-L1 (°) (P <0.05). Conclusions: The study showed that miniscrew-anchored maxillary protraction associated with facemasks and mandibular anchorage bars produces positive skeletal effects in adolescents while also favoring the control of dental effects.